Analisis Semiotika Atas Makna Kesedihan Dalam Lagu “Bunga Terakhir” - Akbar, Mulyono; Fajarini, Sri Dwi (ARKANA: Jurnal Komunikasi dan Media, 2025)
This study aims to analyze the meaning of sadness in the lyrics of the song "Bunga Terakhir" by Bebi Romeo using Ferdinand de Saussure's semiotic approach. The research problem raised is how the meaning of sadness is represented through signs in the lyrics, both syntagmatically and paradigmatically. This research uses a qualitative descriptive method with documentation and observation as data collection techniques. The lyrics are analyzed using Saussure's semiotic structure: syntagmatic relationships (the arrangement of words in the text) and paradigmatic relationships (word choices within possible alternatives). The results show that sadness in this song is not expressed explicitly, but symbolically through the phrase “bunga terakhir” (the last flower), poetic diction, and a structured emotional narrative. Love is depicted as beautiful but must be released sincerely, leaving memories as the eternal space where that love continues to exist. Sadness arises not from rejection, but from the inability to hold on—while still choosing to give and remember.